Stegomyia Indices and Risk of Dengue Transmission: A Lack of Correlation - Garjito, Triwibowo Ambar; Hidajat, Muhammad Choirul; Kinansi, Revi Rosavika; Setyaningsih, Riyani; Anggraeni, Yusnita Mirna; Mujiyanto; Trapsilowati, Wiwik; Jastal; Ristiyanto; Satoto, Tri Baskoro Tunggul; Gavotte, Laurent; Manguin, Sylvie; et al. (Frontiers in Public Health, 2020)
Dengue is one of the the most widespread mosquito-borne arbovirus disease in the world. It is present in 128 countries worldwide with major public health, social and economic consequences and is still expanding. There is currently no treatment or universally approved vaccine available. Therefore, prevention and control of mosquito vectors remain the most efficient ways of managing the risk of dengue outbreaks. The Stegomyia indices have been developed as quantitative indicators of the risk of dengue outbreaks. However, conflictual data are circulating about their efficacy. We report in this article the first extensive, two-year study of Stegomyia indices, covering 78 locations of differing environmental and socio-economic conditions, climate, and population density across Indonesia, from West Sumatra to Papua. A total of 65,876 mosquito larvae were collected for the study. The conclusion, strongly supported by non-parametric statistics, is that there is no correlation between the incidence rate of dengue and any of the Stegomyia indices.